(untitled) (American Journal of Aquaculture and Animal Science, 2023)
Feed additives are regarded as an essential component of the fish diet during the production of fish feed. The addition of feed additives to fish food is essential for enhancing the growth and immunity of farmed fish. This study’s objective was to conduct a comprehensive review of the Current Status and Trends in the Adoption of these fish feed additives for Sustainable Tilapia production. In this study, an exploratory research design was used to review and comprehend numerous peer-reviewed papers published in national and international publications on issues related to fish feed additives currently used in Tilapia aquaculture production and the current and future prospects of essential fish feed additives. Feed additives are ingredients that are added in minor amounts to fish diets to increase nutrient content and prolong shelf life. Preservatives, binders, feeding stimulants, and food coloring are frequent feed additives. In order to optimize the production of farmed fish, it is necessary to encourage the use of additives as aquaculture expands. The purpose of feed additives in fish feed is to promote healthier and more rapid fish growth in aquaculture. As a result, fish diets must include the proper amounts of feed additives. The findings imply that fish feed without feed additives is analogous to “a vehicle without fuel” and should be regarded as poor fish feed when fed to fish in an aquaculture system. The end consequence will be a low growth rate for fish, decreased disease resistance, and consequently low productivity in an aquaculture production system.